2020
DOI: 10.1080/02770903.2020.1753209
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with knowledge of self-management of worsening asthma in primary care patients: a cross-sectional study

Abstract: Objective: Self-management is important for asthma control. We examined associations of patient-and healthcare-related factors with self-reported knowledge of self-management of worsening asthma. Methods: Two asthma patient cohorts from 2012 (n ¼ 527) and 2015 (n ¼ 915) were randomly selected from 54 primary health care centers (PHCC) in central Sweden. Data were collected using patient questionnaires and questionnaires to the PHCCs. Logistic regression analyzed associations of relevant variables with knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Despite well-documented evidence of the positive impact of asthma self-management programmes in achieving the desired patient outcomes and reducing healthcare costs, it is unfortunately rarely implemented in routine clinical practice 1 2 5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite well-documented evidence of the positive impact of asthma self-management programmes in achieving the desired patient outcomes and reducing healthcare costs, it is unfortunately rarely implemented in routine clinical practice 1 2 5…”
Section: Introductionmentioning
confidence: 99%
“…Asthma has over many years become one of the major health concerns affecting millions of people 1 and is defined as a chronic, non-communicable inflammatory disorder of the airways, which affects 334 million people worldwide with an alarming prediction of an increase in 100 million more by the year 2025. 1 2 Considering the most leading causes of disease which burdens society, asthma ranks 28th, causing approximately 1000 people to die every day around the globe. In addition, it ranks 16th among the leading causes of years of life lived with a disability and its prevalence is still rising in underdeveloped countries.…”
Section: Introductionmentioning
confidence: 99%
“…", is not always consistent with the physician's assessment using standardized measures (7). However, the patient's perspective is important, as we also reported that self-assessed moderate or severe asthma is more notably associated with lower selfmanagement skills than poor asthma control, as measured by standardized questionnaires and history of exacerbations (8).…”
Section: Introductionmentioning
confidence: 73%
“…We identified 2824 unique references, of which 36 articles were read in full text. Sixteen articles fulfilled the inclusion criteria, 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 of which one 25 was later excluded because of an unacceptable risk of bias. Of the 15 included articles, 14 were based on observational data, mainly retrospective cohort studies, and one 24 was a randomized controlled study.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies investigated various patient assessments of experience of received care, self-management of disease and quality of life. 20 , 23 , 24 The assessment of continuity of care was only partially relevant and the results were presented in various ways. All results were, however, consistent in their findings that higher relational continuity of care showed a positive association with experience, communication and participation 20 , self-management of the disease 23 and health-related quality of life.…”
Section: Resultsmentioning
confidence: 99%